Scene Text Recognition: A Review - Mageed, Essam Haider; El Abbadi, Nidhal Khdhair (Iraqi Journal of Science, 2023)
The problem of text recognition and its applicability as part of images captured in the wild has gained a significant attention from the computer vision community in recent years. In contrast to the recognition of printed documents, scene text recognition is a difficult problem. Contrary to recognition of printed documents, recognizing a scene text is a challenging problem. Many researches focus on the problem of recognizing text extracted from natural scene images. Significant attempts have been made to address this problem in recent past. However, many of these attempts work on utilizing availability of strong context, which naturally limits the dictionary. This paper presents a review of recent papers related to scene text recognition in the period (2013-2020). This paper helps other researchers to understand the whole system of scene text recognition instead of reading many papers in isolation.